Pengaruh Rekrutmen, Seleksi Berbasis Nilai Islam dan Digitalisasi HR terhadap Kinerja Karyawan : Systematic Literature Review - Suci Nuralita; Rulistya Maharani; Mochamad Reza; Aulia Puspa Ayu; Tini Ulan Dari; Muhammad Saepul Adnan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the influence of Islamic value-based recruitment and selection on employee performance, with HR digitalization as a moderating variable. A Systematic Literature Review (SLR) approach was used by following the PRISMA guidelines to compile, screen, and analyze articles from various national and international academic databases published between 2021 and 2025. From a total of 226 identified articles, 25 met the inclusion criteria and were analyzed further. The findings indicate that most of the reviewed literature supports a positive and significant influence of Islamic value-based recruitment and selection on employee performance, particularly in terms of productivity, work ethics, and loyalty. Furthermore, HR digitalization strengthens the recruitment process by increasing efficiency and objectivity through technologies such as e-recruitment, applicant tracking systems (ATS), and AI based on sharia principles. However, the effectiveness of implementation depends on technological readiness and organizational characteristics. These findings emphasize the importance of integrating spiritual values and digital innovation in Islamic human resource management practices that are adaptive to the challenges of Industry 4.0 and Society 5.0.